The Impact of Flyover Development on Business Income in Surabaya Intersection Area, Banda Aceh - Rizkiya, Putra; Hasan, Zainuddin; Akbar, Muhammad Irfan; Gunawan, Arief; Maulida, Putra (Jurnal Wilayah dan Lingkungan, 2024)
Surabaya Intersection is one of the main intersection with vigorous economic activity in Banda Aceh, Indonesia. Nevertheless, it was also one of the main congestion points during peak hours. Therefore, a flyover infrastructure was develop in 2016 to reduce congestion. With better traffic, the income of business in its surrounding area was expected to rise. However, many business experienced declining conditions and even closed a few years after the construction. This research aims to study the impact of flyover development on the income of business in the Surabaya Intersection area. Data were collected through questionnaires supported by observation and interviews with related agencies and academics. The business income questionnaires were distributed to 100 samples from 320 business in this area , chosen with a purposive sampling technique. The study area was divided into 10 segments based on physical characteristics. The analysis conducted was descriptive quantitative supported by qualitative analysis. The result shows that after the flyover development, the business income declined. The income of business in most of business in most segments (7 of 10 segments) reduced between 3.33% to 27.2%. Only three segments experienced increasing income, ranging between 0.8% to 4%. As shown by interpolation result, all segments located right along the Surabaya Intersection flyover showed a significant decrease in business income. The decline in business income is caused by the lack of parking spaces, difficult interzonal mobility, and decreasing attractiveness. This condition indicates that the flyover development in Surabaya Intersection has caused and unsustainable impact on the business in its surrounding area.